1985
DOI: 10.1002/ana.410180202
|View full text |Cite
|
Sign up to set email alerts
|

Human cutaneous mechanoreceptors during regeneration: Physiology and interpretation

Abstract: Percutaneous microneurography was used to record activity from single cutaneous afferents reinnervating the glabrous skin of the hand. Recordings were obtained from 6 months to 10 years after complete transsection of the median andlor ulnar nerves with subsequent repair. Transitional properties in the discharge behavior and receptive field characteristics of regenerating afferents were detected during the early stages of regeneration, when axonal maturation was still in progress; these may contribute to the sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…23,24 In humans, the characteristics of the rapidly and slowly adapting mechanoreceptors of glabrous skin of the hands have mainly been elucidated using microneurography. 4,8,9 The ultrastructural recovery of mechanoreceptor morphology has been studied in experimental animals, but not in human subjects. 4,8,9 The ultrastructural recovery of mechanoreceptor morphology has been studied in experimental animals, but not in human subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 In humans, the characteristics of the rapidly and slowly adapting mechanoreceptors of glabrous skin of the hands have mainly been elucidated using microneurography. 4,8,9 The ultrastructural recovery of mechanoreceptor morphology has been studied in experimental animals, but not in human subjects. 4,8,9 The ultrastructural recovery of mechanoreceptor morphology has been studied in experimental animals, but not in human subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, clinically meaningful sensory recovery is often unsatisfactory after surgical repair of severed nerves, which may be attributed to: (1) limited outgrowth of fibers, 1 (2) disturbed function of regenerated fibers or reinnervated end organs, 2,3 (3) incorrect reinnervation of receptors, 4,5 and (4) disturbed information processing in the central nervous system (CNS). Reinnervation of Pacinian corpuscles was absent in some studies, 8,9 whereas others showed reinnervation of all types of receptors. Reinnervation of Pacinian corpuscles was absent in some studies, 8,9 whereas others showed reinnervation of all types of receptors.…”
mentioning
confidence: 91%
“…These and other studies in humans and animals have shown (1) that the sensory fields of RA units (Meissner corpuscles) are small and sharply demarcated, whereas those of PC units (Pacini corpuscles) are large and poorly delineated 18,21,26 ; (2) that the RA units at threshold are sensitive to sinusoidal vibration of 5-40 Hz and PC units to vibration of 60-300 Hz 19,32,33,39,42 ; (3) that the threshold to indentation force is similar in RA units and PC units 23 ; (4) that the Meissner corpuscles are placed superficially in the epidermis and the Pacini corpuscles deep in the dermis or subcutis 31,38 ; (5) that the density of Meissner corpuscles increases distally in the fingers, whereas the density of PC corpuscles remains more or less constant in the hand 20 ; (6) that dynamically sensitive slowly adapting receptors have small sensory fields, and that they are situated superficially in the skin; and (7) that the conduction velocities of afferent fibers are similar in the range of large myelinated fibers. 17,25,36 Though microneurography may be used to investigate function of individual receptors in pathological states, such as wallerian degeneration and regeneration 14,35 and diabetes mellitus, 37 the technique is not suitable to delineate the extent of neuropathic processes, due to sampling difficulties when studying single nerve fibers and receptors. The method used in our work applies tactile stimuli to groups of receptors in the skin and relies on electronic averaging technique to record the CSAP from associated nerve fibers.…”
Section: Findings At Tactile Stimulation As Related To Othermentioning
confidence: 99%
“…8,10 Thus our findings are in agreement with other studies that the largest fibers innervating mechanoreceptors in the skin are in the A␣ range. 31 In most previous microneurographical studies, the conduction velocities were calculated from the distal innervation site to the recording site using an electrical current to activate the nerve fiber, 25,35,36 whereas we have excluded the distal part of the nerve by recording the CSAPs at two sites along the nerve. The distal part of the nerve fiber introduces a source of error into the calculation of the conduction velocity, due to the distal reduction in diameter and loss of myelin, which may vary among different fibers.…”
Section: Findings At Tactile Stimulation As Related To Othermentioning
confidence: 99%
“…After isolation from the background or multi-unit activity, cutaneous mechanosensitive afferents were first type identified as RA (rapidly adapting), SAI (slowly adapting type I), SAII (slowly adapting type II) and PC (Pacinian units), according to the criteria of discharge characteristics in response to mechanical skin indentations and according to the receptive field properties (Vallbo et al 1979;Mackel, 1985). Briefly, the RA and PC units adapt quickly to mechanical indentation of their receptive fields.…”
Section: Recording Proceduresmentioning
confidence: 99%